MAN1B1 Deficiency: An Unexpected CDG-II - Rymen, D. (2014)
Congenital disorders of glycosylation (CDG) are a group of rare metabolic diseases, due to impaired protein and lipid glycosylation. In the present study, exome sequencing was used to identify MAN1B1 as the culprit gene in an unsolved CDG-II patient. Subsequently, 6 additional cases with MAN1B1-CDG were found. All individuals presented slight facial dysmorphism, psychomotor retardation and truncal obesity. Generally, MAN1B1 is believed to be an ER resident alpha-1,2-mannosidase acting as a key factor in glycoprotein quality control by targeting misfolded proteins for ER-associated degradation (ERAD). However, recent studies indicated a Golgi localization of the endogenous MAN1B1, suggesting a more complex role for MAN1B1 in quality control. We were able to confirm that MAN1B1 is indeed localized to the Golgi complex instead of the ER. Furthermore, we observed an altered Golgi morphology in all patients' cells, with marked dilatation and fragmentation. We hypothesize that part of the phenotype is associated to this Golgi disruption. In conclusion, we linked mutations in MAN1B1 to a Golgi glycosylation disorder. Additionally, our results support the recent findings on MAN1B1 localization. However, more work is needed to pinpoint the exact function of MAN1B1 in glycoprotein quality control, and to understand the pathophysiology of its deficiency.